A new family, genus and species of Tanaidacea (Crustacea; Apseudomorpha) from the Lower Cretaceous (Aptian) of Chiapas, Mexico: Systematic revisions, including designation of two new Paleozoic families, and paleoenvironmental observations. (October 2020) - Heard, Richard W.; Morales-Núñez, Andrés G.; de Lourdes Serrano-Sánchez, María; Coutiño, Marco A.; Barragán, Ricardo; Vega, Francisco J.
Abstract: A new fossil apseudomorphan tanaidacean, Protoapseudoides espinalensis gen. et n. sp., from the Chiapas Region of Mexico, is described and placed within the new monotypic family Protoapseudoidae. Its description is based on more than 1000 specimens collected from the Lower Cretaceous (Aptian) in laminar dolomites from the El Espinal quarries (Sierra Madre Formation). The presence of a telsonic somite partially fussed, but ventrally distinct indicates that the body form of this new tanaidacean may represent a transitional evolutionary step between fossil Anthracocaridomorpha and the extant Apseudomorpha. The presence of an apparently fused, but a ventrally delineated telsonic somite indicates that the new family may represent a transition of an anthracocaridomorphan to an apseudomorphan body form. A new family, the Protoapseudoidae, is designated to accommodate the unique combination of morphological features exhibited by the new Chiapas species. These features include the presence of a vestigial telson, a blunt subtriangular rostrum, vestigial anterolateral processes on the carapace, and a single male genital cone, coupled with the absence of eye stalks, coxal spine on the first pereopod, and spines or lateral processes on carapace and pereon. This combination of characters distinguishes the new family from all the other known extinct and extant families within the Order Tanaidacea. Though clearly indicated ventrally, unlike the Anthracocaridomorphan, the vestigial telsonic somite of new Chiapas family appears not to be "independent" or "articulated, " and is functionally fused with pleonite-6 to form a pleotelson. Accordingly, the new family is tentatively placed within the suborder Apseudomorpha. The Protoapseudoidae appears, at least superficially, to have possible affinities with both the Paleozoic genus Ophthalmapseudes and to the members of the extant parapseudid Discapseudes - Halmyrapseudes Complex. The Paleozoic monotypic, anthracocaridid genera Eucryptocaris and Ophthalmapseudes, due to their unique morphological features and temporal distances, are hierarchized to family rank. As Eucryptocaridae n. fam. and Ophthalmapseudidae n. fam. Due to their based similarity, the superfamily Jurapseudoidea, is considered a junior synonym of the superfamily Apseudoidea. The possible relationship between the extinction of Protoapseudoidae and the emergence of parapseudid tanaidaceans in Americas is discussed. The morphological changes recorded between the Cretaceous fossil tanaidaceans, including the review of those 25 species as far known, and their extant relatives are considered to propose the timelines on the evolution of different tanaidacean morphotypes. Also, here are discussed the taphonomic and paleoenvironmental Condition that allow the fossil preservation of tanaidaceans. Highlights: New family, genus and species of Early Cretaceous (Albian) Tanaidacea from Mexico. The best preserved association of this kind of crustaceans so far. Morphological details exquisitly preserved allow to compare the new species with other recent and fossil species. Paleoenvironment, posible periodic influence of organic matter (via freshwater), periodical mass mortality events (anoxia).